Nitrogen rates associated with the inoculation of Azospirillum brasilense and application of Si: Effects on micronutrients and silicon concentration in irrigated corn - Galindo, Fernando Shintate [UNESP]; Minhoto Teixeira Filho, Marcelo Carvalho [UNESP]; Buzetti, Salatier [UNESP]; Rodrigues, Willian Lima [UNESP]; Fernandes, Guilherme Carlos [UNESP]; Marcandalli Boleta, Eduardo Henrique [UNESP]; Neto, Mauricio Barco [UNESP]; Campos Biagini, Antonio Leonardo [UNESP]; Baratella, Eduardo Bianchi [UNESP]; Souza, Jeferson Silva de [UNESP] (Sciendo, 2018)
The aim of this study was to analyze whether there are differences between the inoculation with Azospirillum brasilense and the silicon application, thus enabling a higher efficiency of nitrogen fertilization, evaluating micronutrients and silicon concentration in shoots and roots of irrigated corn (Zea mays). The experiment was conducted in Selviria, Brazil, under a no-till system, on a Typic Rhodic Hapludox. The experiment was set up as a randomized block design with four replications, in a 2 x 5 x 2 factorial arrangement consisting of two soil corrective sources (dolomitic limestone and Ca and Mg silicate as source of Si); five N rates (0, 50, 100, 150 and 200 kg ha(-1)); with and without inoculation with A. brasilense. N rates increased B, Cu and Fe concentrations in shoots and B, Cu, Fe, Mn, Zn and Si in roots. Inoculation provided greater concentrations of B and Fe in shoots, and B in roots. Although inoculation with A. brasilense favored micronutrient uptake, it negatively affected Si concentration in shoots in 2015/16 crop. The use of Si in the form of Ca and Mg silicate promotes an increase in Mn, Si and Zn uptake in shoots and Mn and Si concentration in roots.
Keywords: Zea mays; biological nitrogen fixation in grasses; plant growth promoting bacteria; silicon application; efficiency of nitrogen fertilization